The Characteristics of Septic Arthritis Patients at Dr. Kariadi Hospital Semarang - Zulfikar Alem Abdillah Malik (Indonesian Rheumatology Associantion, 2025)
Background: Septic arthritis is an inflammatory disease caused by microbial infections such as bacteria, fungi, and viruses. Late diagnosis can lead to permanent joint damage, while overdiagnosis may result in unnecessary medical procedures. Although the incidence is relatively low, septic arthritis remains a medical concern due to its impact on joint function and patient quality of life. Determining the characteristics is needed to improve the diagnosis, treatment strategies, and prognosis of septic arthritis. Methods: This descriptive study utilized a retrospective design and was conducted on adult patients diagnosed with septic arthritis at dr. Kariadi General Hospital, Semarang, from January 2017 to August 2023. The analyzed variables included clinical manifestations, comorbidities, laboratory test results, synovial fluid analysis, synovial fluid culture, and antibiotic resistance. Results: Among the 49 patients, most were under 60 years old (67.4%) and male (61.2%). The knee joint was the most commonly affected site (87.8%) with the main symptoms such as joint pain, edema, and reduced range of motion (100%), along with inflammatory signs such as joint warmth (89.9%) and redness (83.7%). Synovial fluid analysis revealed that 53.06% of patients had cloudy and foul-smelling synovial fluid, with an average white blood cell count of 93,679.43/mm³ and a predominance of neutrophils (80.37%). Synovial fluid culture identified Staphylococcus aureus as the most common pathogen (34.7%), followed by Klebsiella pneumoniae (4.1%) and Salmonella sp. (2%). Antibiotic sensitivity tests showed Ampicillin/Sulbactam as the most effective treatment, while antibiotic resistance was observed in Gentamicin, Penicillin, and Linezolid. Conclusion: Staphylococcus aureus is the dominant pathogen, and rising antibiotic resistance remains a concern. Early diagnosis and targeted therapy are crucial for better patient outcomes.